Epigenetic regulation of leptin affects MMP‐13 expression in osteoarthritic chondrocytes: possible molecular target for osteoarthritis therapeutic intervention - Iliopoulos, D (BMJ Group, 2007)
OBJECTIVE: To investigate whether epigenetic mechanisms can regulate leptin's expression and affect its downstream targets as metalloproteinases 3,9,13 in osteoarthritic chondrocytes. METHODS: DNA methylation in leptin promoter was measured by DNA bisulfite sequencing, and mRNA expression levels were measured by real‐time quantitative PCR in osteoarthritic as well as in normal cartilage. Osteoarthritic articular cartilage samples were obtained from two distinct locations of the knee (n = 15); from the main defective area of maximum load (advanced osteoarthritis (OA)) and from adjacent macroscopically intact regions (minimal OA). Using small interference RNA, we tested if leptin downregulation would affect matrix metalloproteinase (MMP)‐13 activity. We also evaluated the effect of the demethylating agent, 5′‐Aza‐2‐deoxycytidine (AZA) and of the histone deacetylase inhibitor trichostatin A (TSA) on leptin expression in chondrocyte cultures. Furthermore, we performed chromatin immunoprecipitation in leptin's promoter area. RESULTS: We found a correlation between leptin expression and DNA methylation and also that leptin controls MMP‐13 activity in chondrocytes. Leptin's downregulation with small interference RNA inhibited MMP‐13 expression dramatically. After 5‐AZA application in normal chondrocytes, leptin's methylation was decreased, while its expression was upregulated, and MMP‐13 was activated. Furthermore, TSA application in normal chondrocyte cultures increased leptin's expression. Also, chromatin immunoprecipitation in leptin's promoter after TSA treatment revealed that histone H3 lysines 9 and 14 were acetylated. CONCLUSION: We found that epigenetic mechanisms regulate leptin's expression in chondrocytes affecting its downstream target MMP‐13. Small interference RNA against leptin deactivated directly MMP‐13, which was upregulated after leptin's epigenetic reactivation, raising the issue of leptin's therapeutic potential for osteoarthritis.